Para ser e deixar-de-ser: arte e vida na pós-história - Thiago Reis dos Santos (2018)
In view of Vilém Flusser's predictions about the need for new situations to arise in order to in-form and update reality, we aim to emphasize the importance of the aesthetic dimension in the author's philosophical project, approaching it as an interpretive spectrum. As is known, art takes on a key role in addressing the notion of post-history in Flusser's theory. This is because in post-historical reality dominated by apparatuses that operate by stupid inertia, accentuating the entropic (and, therefore, boring) character of existence art is presented as a sphere of human communication capable of destabilizing a certain homogeny (and reifying) trend, which is founded on "apparatus-based" functionalization of the social fabric. From that point on, we aim to present two perspectives with respect to the aesthetic dimension in Flusserian theory: (i) the role of art against 'letting it be', rectifying the need for engagement against dehumanization and, (ii) the role of art for 'letting it be' and the need for reinventing the forms of human existence.